2014
DOI: 10.1111/fpa.12038
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sanctions, International Institutions, and Sanctions Busters: When Does Institutionalized Cooperation Help Sanctioning Efforts?

Abstract: When international institutions obligate their members to impose economic sanctions against a target state, how much do those sanctions obligations actually impact their members' behavior? To date, the consensus view has treated all international institutions as if they are equally capable of making multilateral sanctioning efforts more effective. Building upon the enforcement theory of sanctions cooperation, we instead theorize that the ability of international institutions to constrain their members from eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…More specifically, international institutions can require their member states to submit self-reports on their compliance with the sanctions regime or directly monitor targets’ borders to detect economic exchanges violating the sanctions regime. Rent-seeking private sector entities of member states tend to limit the size of their trade with targets to avoid detection (Early and Spice 2015; Hastings and Wang 2018; Wertz 2020).…”
Section: Senders’ Incentives To Pursue Institutional Support: Respons...mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, international institutions can require their member states to submit self-reports on their compliance with the sanctions regime or directly monitor targets’ borders to detect economic exchanges violating the sanctions regime. Rent-seeking private sector entities of member states tend to limit the size of their trade with targets to avoid detection (Early and Spice 2015; Hastings and Wang 2018; Wertz 2020).…”
Section: Senders’ Incentives To Pursue Institutional Support: Respons...mentioning
confidence: 99%
“…Institutional support can promise primary senders substantial benefits, especially when they are concerned that sanctions-busting by third party states might ruin their foreign policy initiatives. When senders implement sanctions through the international institutions to which potential spoiler states belong, a multitude of institutional restrictions may place tangible constraints on their sanctions-busting behaviors (Early and Spice 2015; Hastings and Wang 2018; Wertz 2020). Even if third-party states indeed violate sanctions regimes, institutional support can still play a key role in countering sanctions-busting.…”
Section: Senders’ Incentives To Pursue Institutional Support: Respons...mentioning
confidence: 99%
“…Iran and Syria are covered by the pathway, too, however, not uniquely. From a theoretical perspective, the pathway is plausible as we know from scholarly research on sanctions that multilateral coalitions of restrictive measures make the latter more likely prone to success (Bapat & Morgan, 2009;Early & Spice, 2015;Weber & Schneider, 2020). Hence, the EU may take the potential support by further actors like the US into account when making design decisions on economic sanctions regimes.…”
Section: Analyzing Design Decisions On International Sanctionsmentioning
confidence: 99%
“… 6 A series of in-depth case studies have concluded that some of these UN sanctions were effective: Angola, Liberia, Sierra Leone, and Côte d’Ivoire (Cortright & Lopez, 2000, 2002a,b; Hufbauer & Oegg, 2000; Koddenbrock, 2008; Strandow, 2006). In contrast, some have questioned sanctions successes and point to cases such as Rwanda, Sudan, and Somalia to suggest the UN sanction regimes’ ineptness (Early & Spice, 2014; Elliott, 2005; Tierney, 2005; Vines, 2012). Biersteker, Eckert & Turinho (2016) put the overall UN sanction regime effectiveness near 23%, which is lower than the already meager 30–35% success rate for sanctions overall (Hufbauer et al, 2007).…”
mentioning
confidence: 99%
“… 9 See Early & Spice (2014) for sanction-busting on multilateral efforts. …”
mentioning
confidence: 99%